2022
DOI: 10.1186/s12903-022-02652-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the London Atlas, Willems, and a new quick method for dental age estimation in Chinese Uyghur children

Yueting Lin,
Nuerbiyamu Maimaitiyiming,
Meizhi Sui
et al.

Abstract: Background Numerous dental age estimation methods have been devised and practised for decades. Among these, the London Atlas and Willems methods were two of the most frequently adopted, however dependent on atlantes or tables. A new estimation method less reliant on external measurement could be efficient and economical. Aim This study aimed to evaluate the utility and applicability of the dental age estimation methods of London Atlas, Willems, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Various studies have explored the applicability of this method in their respective populations, yielding promising results. (46)(47)(48) 2. between open apices, N0, and age. (49) In instances where the roots of all seven permanent teeth roots are fully closed, attention turns to the third molars, the last teeth to develop.…”
Section: Atlas Of Human Tooth Development and Eruption Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have explored the applicability of this method in their respective populations, yielding promising results. (46)(47)(48) 2. between open apices, N0, and age. (49) In instances where the roots of all seven permanent teeth roots are fully closed, attention turns to the third molars, the last teeth to develop.…”
Section: Atlas Of Human Tooth Development and Eruption Methodsmentioning
confidence: 99%
“…A review of studies published in the Pubmed database 84 studies were excluded due to the criteria, in total, 71 studies underwent thorough assessment. (6,23,32,45,47,48, The publication count being at its highest in 2022 and following by in 2021 and 2020. Furthermore, the objective was to locate the most recent trend studies, which prompted the inclusion of studies up to 2023.…”
Section: Current Trends Of the Radiology-based Age Estimationmentioning
confidence: 99%
“…The LD is generally regarded as simpler, faster, and more intuitive than the scoring techniques. Various populations have validated the LD [ 9 , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ], however, no studies have reported the applicability of LD in the Korean population, necessitating its validation before its implementation in Korean forensic practice. This study aimed to assess the suitability of the LD for Koreans in forensic practice by analyzing its bias and accuracy.…”
Section: Introductionmentioning
confidence: 99%